Pelatihan Pembuatan Aplikasi Menggunakan Netbeans IDE - Agung Apriansyah; Fathi Rizki Ammar; Mohammad Syibro Malisie; Siva Fauziyah; Eko Heriyanto; Salvia Anggraini; Rinna Rachmatika; Fauzi Maulana Akbar (CV. Multi Kreasi Media, 2023)
SMK Letris 2 Indonesia is one of the favorite vocational schools in Pd. Benda, Kec. Pamulang, South Tangerang City. In the era of the industrial revolution 4.0 which is increasingly developing, technology is increasingly influential in every life, including in the world of education. From these considerations, an idea arose to provide Java Netbeans programming training to Letris 2 Indonesia Vocational High School students to become qualified Java programmers and be able to compete in the world of work. This training was held at SMK Letris 2 Indonesia in the IT department which included TKJ and RPL. The training was held for 1 day by lecturers and students of Informatics Engineering, University of Pamulang. The students directly did practice with their respective computers or laptops, during the project session they succeeded in making individual project programs.